An overview of traditional Malay medicine in the Malaysian healthcare system - Raja Ikram, Raja Rina; Mohd Khanapi, Abd Ghani (ansinet, 2015)
This study shall provide an overview of Traditional Malay Medicine in the Malaysian Healthcare System. A literature review was done from journal databases, identify miscellaneous books, publications and organisation websites that provide services related to traditional Malay medicine. The search generated 32 results from over 2000 articles screened using the inclusion criteria. Articles reviewed can be divided into a few characteristics including case study of usage of TMM herbs on clinical diseases, role of traditional Malay healers in society, society perception and acceptance towards Malay medicine and regulation requirements for complementary medicine. The results have been summarised and categorised according to the parameters of two models, the healthcare system framework and doctor patient consultation framework. Formal training of practitioners and future recommendations of the Traditional Malay Medicine industry is also discussed.